Effect of Dominant Fatty Acid Esters on Emission Characteristics of Waste Animal Fat Biodiesel in CI Engine - Jambulingam, Ranjitha; Shankar, Vijayalakshmi; Palani, Shalini; Srinivasan, Gokul Raghavendra (Frontiers in Energy Research, 2019)
This present study aims in understanding the influence of dominant fatty acid esters of waste animal fat biodiesel on its emission characteristics in CI engine. Biodiesel was produced from waste animal fat by means of base catalysed transesterification; and Ethyl oleate (40.21%), ethyl palmitate (25.36%) and ethyl stearate (16.87%) were characterized as dominant fatty acid esters using GC spectra. Test samples were prepared for these ester molecules based on their availability, in addition to biodiesel blend and plain diesel and were tested for their emission levels in single cylinder four stroke CI engine using flue gas analyser. High exhaust gas temperature was contributed by Ethyl oleate (1.15% lesser than biodiesel), as a result of low cetane number due to unsaturation and high viscosity. Likewise, the increased carbon chain length and unsaturation of ethyl oleate (2.55% lesser than biodiesel) resulted in high concentration of CO emission for biodiesel whereas high CO2 emission concentration was because of ester molecules with increased carbon chain length (stearate and Oleate esters). Reduced NOX emission for biodiesel was as a result of higher cetane number from ethyl stearate (CN=86.83) and ethyl palmitate (CN=86.55), which reduced its ignition delay thereby moderating the heat release rate. In addition, long carbon chained ester molecules (oleate and stearate esters) in biodiesel consumed more oxygen content for improving overall rate of combustion while increased HC emission was explained by unsaturation in biodiesel because of ethyl oleate (on average ,50 PPM).